Enraizamento de estacas de aceroleira ( Malpighia ermarginata DC.) em diferentes substratos e eficiência de fungos micorrízicos arbusculares na formação de mudas - Pinheiro, Eduardo Mendonça (2017)
The culture of acerola (Malpighia emarginata D.C.) due to its high content of vitamin C, has aroused great economic interest and with great potential for expansion. But due to the unevenness of its orchards has been generating negative characteristics in the production of acerola. The objective of this study was to evaluate the effect of different substrates (plantimax, vermiculite, soil + chicken manure) on the rooting of herbaceous and semilenous cuttings of acerola plants and through inoculation with arbuscular mycorrhizal fungi (Claroideoglomus etunicatum - Claetun, Gigaspora margarita - Gimarg and Glomus clarum - Glclar and their combinations) to analyze its effect on the growth rates of greenhouse seedlings at the State University of Maranhão with an intermittent misting system. The statistical design was completely randomized, and in the first phase the 2 x 4 factorial scheme was used, two types of cuttings and 4 substrates with 8 replications in the 60 day experiment period and in the second phase 2 x 8 factorial scheme, Two types of cuttings (herbaceous and semilenous) and 7 inoculations and 1 control, forming 16 treatments in the period of 100 days of experiment. In the first phase the percentage of rooting, length of roots, number of new leaves formed and height of seedling were evaluated. In the seedling inoculation phase the development of mycorrhizal seedlings (height and fresh and dry mass of shoots and roots), positive correlations between growth characteristics of the plant, relative and absolute growth rate, and the rate of mycorrhizal colonization Through the methodology of Giovannetti and Mosse (1980). The herbaceous cuttings in vermiculite substrate obtained a higher percentage of rooting (86.25%), higher root mean length (5.30 cm), higher seedling height and formation of new leaves. The inoculation with Gigaspora margarita + Claroideoglomus etunicatum promotes greater growth in acerola plants derived from herbaceous cuttings and in plants derived from semilenous cuttings, its growth is favored by the inoculation of Claroideoglomus etunicatum.